2022
DOI: 10.2196/33926
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Telemedicine Use for Anesthesiology Pain Division: Retrospective, Observational Case Series Study

Abstract: Background An increasing number of patients require outpatient and interventional pain management. To help meet the rising demand for anesthesia pain subspecialty care in rural and metropolitan areas, health care providers have used telemedicine for pain management of both interventional patients and those with chronic pain. Objective In this study, we aimed to describe the implementation of a telemedicine program for pain management in an academic pain division in a la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…This could be attributed to multiple factors, which have been mentioned in previous publications, including the convenience of receiving care from the comfort of one’s home and the elimination of travel and wait time. 16 , 21 , 22 This is further supported when looking at the results from the regression analysis ( Table 4 ), demonstrating a significant association between residing outside of Manhattan and the utilization of telemedicine. In contrast, patients residing in Manhattan – in proximity to the locations examined in the study, but also an area well served by public transportation - preferred in-office visits post-lockdown.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This could be attributed to multiple factors, which have been mentioned in previous publications, including the convenience of receiving care from the comfort of one’s home and the elimination of travel and wait time. 16 , 21 , 22 This is further supported when looking at the results from the regression analysis ( Table 4 ), demonstrating a significant association between residing outside of Manhattan and the utilization of telemedicine. In contrast, patients residing in Manhattan – in proximity to the locations examined in the study, but also an area well served by public transportation - preferred in-office visits post-lockdown.…”
Section: Discussionsupporting
confidence: 57%
“… 21–23 With its crux focused on connecting patients with healthcare providers via video-enabled virtual visits, telemedicine eliminated travel-related costs and reduced the burden of travel time, thereby ameliorating some traditional access-level barriers to treatment while maintaining patient satisfaction. 18 , 22 , 24 …”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Jalilian et al found that 92% of patients seen via telemedicine within a pain division at an urban academic medical center were satisfied with their care via telemedicine. 58 Another study by Harnik et al found patients’ acceptance of telemedicine during the COVID-19 pandemic was high overall but lower among those with levels of pain and anxiety higher than the mean indicating telemedicine may not suffice for this subgroup. 59 Another recent narrative review detailed best practices for telehealth use and remote physical examinations.…”
Section: Discussionmentioning
confidence: 99%
“…The field of anesthesiology was no exception; the American Society of Anesthesiologists (ASA) and the American College of Surgeons (ACS) officially called for the utilization of teleconsultations for preoperative evaluations to maintain medical services while limiting disease transmission [7,8]. Additionally, anesthesiologists increasingly utilized telemedicine for pain management in both rural and urban healthcare settings [9]. The in-person preoperative anesthesia consultation serves multiple purposes including patient education, optimization of comorbid conditions, and perioperative risk reduction [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%